Social Protection in times of COVID-19: experiences in Latin America - Senna, Mônica de Castro Maia; Maior, Aline Souto; Suárez Baldo, Valentina (Argumentum, 2021)
The article addresses experiences in adopting social protection measures in the face of the COVID-19 pandemic in Latin America, focusing on Argentina, Mexico, and Brazil. The central argument is that the pandemic requires social protection measures, but that it comes up against the structural constraints of their systems. Thus, the health crisis aggravates these profound social inequalities. Converging points, singularities and challenges for their social protection systems Have been identified, and we conclude that the responses implemented, which have emphasized income security, emergency aid to individuals/ families and/or aid to productive sectors, are insufficient. It is essential to link them with comprehensive social protection measures that strengthen the State to guarantee universal citizenship rights, such as health, protected work, and a basic income.